The Assyrian Dictionary of the Oriental Institute of the University of Chicago. Volume 11: N. Part I-II (1980)
Erica Reiner, Editor-in-Charge - Robert D. Biggs, Associate Editor - with the assistance of Brigitte Groneberg, Hermann Hunger, Johannes Renger, Kaspar K. Riemschneider†, and Marten Stol. - Manuscript Editor, Peter T. Daniels; ersch. 1981; DM 256,-.